Placebo controlled comparative study of oral midazolam and oral ketamine as a premedication in paediatric age group - Longani, Somnath; Mall, Krishna Pratap; Raval, Dipak (International Journal of Advances in Medicine, 2017)
Background: Preanaesthetic medication can play an important part in the anaesthetic care of infants and children. It plays a vital role during induction and maintenance of anaesthesia as well as in post-operative period. Methods: Ninety pediatric patients of ASA status I and II operated for routine surgical procedures at GGH, Jamnagar, Gujarat were studied for the comparision of oral midazolam and oral ketamine as a premedication. The paediatric patients were divided into 3 groups, group M oral midazolam, group K oral ketamine and group P placebo (honey) of 30 patients each. Results: All the patients were given general anaesthesia with injection sodium thiopentone 4 to 5 mg/kg and inj. succinylcholine 1.5 mg/kg and maintained with inj. vecuronium and traces of halothane. Paracetamol rectal suppository 10 to 15 mg/kg was inserted before reversal for post-operative analgesia. All patients were reversed with inj. neostigmine 50 μg/kg and inj. glycopyrrolate 8 μg/kg given intravenously slowly. Intraoperative pulse rate, blood pressure, SPO2 and ECG were recorded. Post operatively apart from vitals sedation score and anxiety score were recorded. The result analysed showed that sedation and anxiolysis was better in ketamine group both during separation from parents and I.V. cannulation. Recovery was smooth in ketamine group whereas recovery in midazolam group was associated with irritability and crying. Conclusions: Oral ketamine is better premedication than oral midazolam in paediatric patients.